Contemporary Logistics in China Collaboration and Reciprocation (Current Chinese Economic Report Series,, 2018)
This book is the eighth volume in a series entitled "Contemporary Logistics in China," authored by researchers from the Logistics Research Center at Nankai University. In the spirit of the seven preceding annual volumes, this book carries on the ideal of providing a systematic exposition on the logistics development in China for the English-speaking community at large. Specially, this volume captures China's logistics development at a crucial turning point. This present report consists of ten chapters, organized into three sections. The introductory section, consisting of three chapters, depicts the current development status of the logistics market, the logistics facilities and technology, and the regional logistics market. The second section addresses the logistics characteristics of four rapidly expanding industries in China-the third-party logistics, the highway logistics, the express logistics, and the multimodal transport. The final section, consisting of three chapters, discusses some hot logistics topics in China. Chapter 8 studies the capital operation in China's logistics industry. The next chapter deals with the development of intelligent logistics in China. The last chapter of this section presents the development of regional logistics along the Belt and Road routes. As with the previous volumes, the ultimate aim of this book is to present a timely portrait of the rapid growth of China's logistics market and the status quo of its logistics industry. In so doing, the book offers an in-depth analysis of critical issues involved in the ongoing dynamic and multi-faceted development, and provides a valuable reference resource for interested readers in the academic and professional fields.